Answer: 0.00102%
Step-by-step explanation:
Given : Human body temperatures are normally distributed with a mean of
and a standard deviation of ![s=0.61^{\circ}F](https://tex.z-dn.net/?f=s%3D0.61%5E%7B%5Ccirc%7DF)
A hospital uses
as the lowest temperature considered to be a fever.
Let x be the random variable that represents the human body temperatures.
![z=\dfrac{x-\mu}{s}](https://tex.z-dn.net/?f=z%3D%5Cdfrac%7Bx-%5Cmu%7D%7Bs%7D)
For x= 100.6, ![z=\dfrac{100.6-98}{0.61}=4.26229508197\approx4.26](https://tex.z-dn.net/?f=z%3D%5Cdfrac%7B100.6-98%7D%7B0.61%7D%3D4.26229508197%5Capprox4.26)
Using normal distribution table for z-values for right-tailed area ,
P(x>100.6)=![P(Z>4.26)=0.0000102=0.00102\%](https://tex.z-dn.net/?f=P%28Z%3E4.26%29%3D0.0000102%3D0.00102%5C%25)
Hence, the required probability = 0.00102%
Y=-2x+0 reason: rise over run as you can see in the graph -2 rise (drop) and -1 run and b=0 y intercept
First find the area of the rectangle, then remove the circular area.
AB * AJ = 8 * 18 = 144 sq cm
Circle =
![\pi r^{2}](https://tex.z-dn.net/?f=%20%5Cpi%20r%5E%7B2%7D%20)
=
![\pi 4^{2}](https://tex.z-dn.net/?f=%20%5Cpi%204%5E%7B2%7D%20)
=3.14 * 16
=50.24 sq cm
144 - 50.24 = 93.76 sq cm shaded area.
To do this problem you would first need to factor out a variable, which in this case I would want to do the first equation because it is isolated. Now the equations would look like this:
x = -2y - 1
4x - 4y = 20
Since we know that x is now equal to -2y - 1 we can plug it in to the x value in the second equation:
4 (-2y -1) - 4y = 20
-8y -4 - 4y
-12y - 4 = 20
-12y = 24
y = -2
Now that we know the y value plug the y value to one equation to find the x, I will be using the first equation
x + 2(-2) = -1
x - 4 = -1
x = 3
Solutions:
y = -2
x = 3
Answer:
x = 3 && y = - 1
Step-by-step explanation:
Just solving the two equations
the first equation
y = 4/3 x +3
y - 4/3 x = 3 ..............................................(1)
the second equation
y = -2/3x -3
y + 2/3 x = -3 ..............................................(2)
by substracting 2 from 1
-4/3x - 2/3x = -6
divide by -1
4/3x +2/3x = 6
6/3x = 6
2x = 6
x= 3
then subsititute by value x in any of given eqautions